2004
DOI: 10.1164/rccm.200404-455oc
|View full text |Cite
|
Sign up to set email alerts
|

C-type Natriuretic Peptide Ameliorates Monocrotaline-induced Pulmonary Hypertension in Rats

Abstract: C-type natriuretic peptide (CNP) has been shown to act as a local regulator of vascular tone and remodeling. We investigated whether CNP ameliorates monocrotaline (MCT)-induced pulmonary hypertension in rats. Rats received a continuous infusion of CNP or placebo. Significant pulmonary hypertension developed 3 weeks after MCT. However, infusion of CNP significantly attenuated the development of pulmonary hypertension and vascular remodeling. Neither systemic arterial pressure nor heart rate was altered. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 36 publications
3
39
0
1
Order By: Relevance
“…36,37 In line with these findings, we observed that lack of EpoR expression on pulmonary endothelium accelerates pulmonary vascular remodeling in EpoR Ϫ/Ϫ rescued mice; this occurrence may be partly due to the lack of direct effects of Epo on pulmonary endothelial cells. 38 -40 By contrast, the expression of EpoR was upregulated by hypoxia in wild-type mice.…”
Section: Epo Has Direct Protective Effects On Pulmonary Endothelial Csupporting
confidence: 81%
“…36,37 In line with these findings, we observed that lack of EpoR expression on pulmonary endothelium accelerates pulmonary vascular remodeling in EpoR Ϫ/Ϫ rescued mice; this occurrence may be partly due to the lack of direct effects of Epo on pulmonary endothelial cells. 38 -40 By contrast, the expression of EpoR was upregulated by hypoxia in wild-type mice.…”
Section: Epo Has Direct Protective Effects On Pulmonary Endothelial Csupporting
confidence: 81%
“…Gene transfer with endothelial nitric oxide synthase attenuated MCT-induced pulmonary hypertension in rats (28). Other pharmacologic treatments that were effective in this PAH model were also associated with an upregulation of eNOS (3,24,25). Thus, the therapeutic effects of CYP2J2 delivery on pulmonary hypertension may be mediated by protection of the endothelium through a restoration of the expression of eNOS, at least in a part.…”
Section: Discussionmentioning
confidence: 83%
“…The pathologic changes of PAH include endothelial cell injury and apoptosis, medial hypertrophy, infiltration by inflammatory cells, and thrombosis in small pulmonary arteries (2,3). Endothelial dysfunction is characterized by an imbalance of vasodilator and vasoconstrictor factors, including an altered ratio of thromboxane and prostacyclin, decreased expression of endothelial NO synthase (eNOS), and increased endothelin-1 (ET-1) (4).…”
mentioning
confidence: 99%
“…CNP is a member of the natriuretic peptide family (Margulies and Burnett, 2006;Lumsden et al, 2010;Baliga et al, 2012) and is widely expressed in various tissues, including the vasculature, especially by the endothelial cells (Baliga et al, 2012;Moyes et al, 2014). CNP is thought to exert an overall vascular protective role: it can fine-tune vascular cell growth (Khambata et al, 2011), establish tone and flow in resistance arteries (Villar et al, 2007;Lumsden et al, 2010), influence vessel wall remodeling (Itoh et al, 2004;Moyes et al, 2014), accelerate re-endothelialization (Ohno et al, 2002), or reduce inflammation (Itoh et al, 2004;Lumsden et al, 2010;Moyes et al, 2014). In contrast to CNP-triggered vasodilatation, directly linked to its stimulation of K ATP activity (Burley et al, 2014), the mechanisms underlying CNP's angiogenic effects are still poorly characterized.…”
Section: Discussionmentioning
confidence: 99%